2021
DOI: 10.1039/d1cc01408k
|View full text |Cite
|
Sign up to set email alerts
|

Solvation vs. surface charge transfer: an interfacial chemistry game drives cation motion

Abstract: Electrolyte structure and ion solvation dynamics determine ionic conductivities, and ion (de)solvation processes dominate interfacial chemistry and electrodeposition barriers. We elucidate electrolyte effects facilitating or impeding Li+ diffusion and deposition,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…We note that in the LCE, the anion is not always present in the cation solvation shell. However, the LCE free energy profile reported here (in the presence of the anion) is similar to the earlier report for carbonates, 34 where the anion was not present. For HCEs, the solvation shells may be populated by an even higher number of anions, but the results shown here illustrate the most important effect that comes from the insertion of the solvation shell in a 3D highly interconnected network.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We note that in the LCE, the anion is not always present in the cation solvation shell. However, the LCE free energy profile reported here (in the presence of the anion) is similar to the earlier report for carbonates, 34 where the anion was not present. For HCEs, the solvation shells may be populated by an even higher number of anions, but the results shown here illustrate the most important effect that comes from the insertion of the solvation shell in a 3D highly interconnected network.…”
Section: Discussionsupporting
confidence: 91%
“…In previous work 34 based on LCEs we found that depending on the electrolyte chemistry, mass transport or electrochemical kinetics may be the limiting step. This is because the solvent 34 and anion (shown in this work) have electron affinities that compete with that of the cation. If the electrolyte components are reduced first, the cation can continue to electrodeposition (in the earlier stages of SEI formation) with mass transport being the rds.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, the research presented here provides thermodynamics and kinetics of nucleation and growth that are useful for the development of coarse-grained models (for example, Kinetic Monte Carlo) and also for force field development for classical molecular dynamics simulations. In addition, a crucial need in battery research is the understanding of ion transport through SEI layers, using methods such as constrained-molecular dynamics [74,75] that require knowledge of the detailed structure and morphology of the growing phase as shown in this work.…”
Section: Discussionmentioning
confidence: 99%